Studi In Silico Kandungan Senyawa Daun Srikaya (Annona squamosa L.)Terhadap Protein Dihydrofolate Reductase Pada Mycobacterium tuberculosis - Nur Cholis Endriyatno; Muhammad Walid (Universitas Muhammadiyah Surakarta, 2022)
Tuberculosis is caused by the Mycobacterium tuberculosis. Tuberculosis is one of the problems in the world, especially the problem of resistance which requires the search for new alternative drugs, one of which is from natural compounds.In silico studies with molecular docking method can be used as a preliminary test to assess the potency of a natural compound. In this study, the target proteins were Dihydrofolate Reductase: 4KL9 and 4KM2 with the original P33 and ATR ligands on Mycobacterium tuberculosis. Dihydrofolate reductase is a protein that has an important role in nucleotide biosynthesis, and has become a target for antibacterial drugs. The natural compounds tested were anonaine, asimilobine, and corypalmine contained in soursop leaves. The molecular docking results showed that the three compounds had docking score, especially for the 4KL9 target protein, which was lower than the original ligand. A lower value means that the binding of the ligand and target protein is stronger than that of the native ligand. The three compound ligands on the target protein 4KM2 have a higher docking score than the original ligand, meaning that the binding of the three ligands is not as strong as the original ligand, but the values are not far apart. In addition, there are similar residues involved from the original ligand and the ligands of the three compounds to the target protein. Therefore, it can be concluded based on an in silico study of the content of anonaine, asimilobine, and corypalmine compounds that may have antituberculosis activity.